2021
DOI: 10.30659/e.6.2.256-269
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing test items analysis to examine the level of difficulty and discriminating power in a teacher-made test

Abstract: Apart from teaching, English language teachers need to assess their students by giving a test to know the students� achievements. In general, teachers are barely conducting item analysis on their tests. As a result, they have no idea about the quality of their test distributed to the students. The present study attempts to figure out the levels of difficulty (LD) and the discriminating power (DP) of the multiple-choice (MC) test item constructed by an English teacher in the reading comprehension test utilizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…We can estimate the difficulty of the problem by determining the percentage of students who choose the correct answer or work on the correct question. The simplest procedure is to base this estimate only on students belonging to the item analysis group (Karim et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We can estimate the difficulty of the problem by determining the percentage of students who choose the correct answer or work on the correct question. The simplest procedure is to base this estimate only on students belonging to the item analysis group (Karim et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The level of difficulty done to know the difficulty level so the questions meet good quality test of the items. The discrimination power shows how well the question differentiates students who are well-versed in the subject from those who are not (Karim, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Difficulty index is one of the key parameters of item analysis. The interpretation of the item difficulty index (Karim et al, 2021;Sharma, 2021), are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%